New Technique to Enhance the Shear Performance of RC Deep Beams Using Mild Steel Plates - M. Mhalhal, Jasim; S. Al-Gasham, Thaar; A. Jabir, Hussain (International Journal of Engineering and Technology, 2018)
This study suggested a new technique to improve a behavior of RC deep beams using mild steel plates as a vertical web reinforcement rather than the conventional rebars. Nine simply supported RC deep beams were tested under the effect of four-point load with a ratio of shear span to an effective depth (a/d) ranged from 0.75 to 1.75 at intervals of 0.5. The test specimens were divided into three groups, each one included three beams. The first group included specimens with conventional vertical web reinforcement. The second and third groups included specimens with mild steel plates as the vertical web reinforcement. The mild steel plates in the second and third groups were configured as strips and sheets, respectively. All the specimens had a length of 1200 mm, a clear span of 900 mm, and a rectangular cross-section of 150 mm wide and of 300 mm depth. The test results confirmed that both of mild steel plate configurations contributed effectively in improving the ultimate load capacity of tested beams, compared with those of conventional shear re-bars, by about (15.4% to 28.26%) and the ductility factor by about (6.06% to 30.56%). Furthermore, specimens with mild steel plates had a low sectional height under tension by about (10.11% to 32.08%).Â Â